2002
DOI: 10.1002/jqs.676
|View full text |Cite
|
Sign up to set email alerts
|

Norwegian sea‐surface palaeoenvironments of marine oxygen‐isotope stage 3: the paradoxical response of dinoflagellate cysts

Abstract: M. 2002. Norwegian sea-surface palaeoenvironments of marine oxygen-isotope stage 3: the paradoxical response of dinoflagellate cysts.ABSTRACT: High-resolution marine palynological data have been obtained from two very long sediment cores (MD952009 and MD952010) retrieved from the southern Norwegian Sea. The dinoflagellate cyst assemblages show pronounced fluctuations in composition, which correlate strongly with magnetic susceptibility records and also mimic the δ 18 O signal of the GISP2 Greenland ice-core. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
40
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(49 citation statements)
references
References 36 publications
8
40
1
Order By: Relevance
“…S6 for further details). We provide here new sea-surface reconstructions for cores MD95-2009, MD95-2010and MD99-2281 based on previously published dinocyst counts (Eynaud et al, 2002;Eynaud, 2003a, b;Zumaque et al, 2011) and extend the previously published reconstructions for core MD99-2285 (Wary et al, 2016; see also Wary et al, 2017 for the complete raw dinocyst counts of core MD99-2285). Our statistical approach provides direct and quantitative reconstructions for mean summer and mean winter SST (with, in the present case, root mean square errors of prediction -RMSEP -of 1.5 and 1.05 • C, respectively), mean summer and mean winter sea-surface salinities (SSS; respective RMSEP of 2.4 and 2.3 psu), and mean annual sea-ice cover (SIC) duration (RM-SEP of 1.2 months year −1 ).…”
Section: Sea-surface Conditionsmentioning
confidence: 56%
See 2 more Smart Citations
“…S6 for further details). We provide here new sea-surface reconstructions for cores MD95-2009, MD95-2010and MD99-2281 based on previously published dinocyst counts (Eynaud et al, 2002;Eynaud, 2003a, b;Zumaque et al, 2011) and extend the previously published reconstructions for core MD99-2285 (Wary et al, 2016; see also Wary et al, 2017 for the complete raw dinocyst counts of core MD99-2285). Our statistical approach provides direct and quantitative reconstructions for mean summer and mean winter SST (with, in the present case, root mean square errors of prediction -RMSEP -of 1.5 and 1.05 • C, respectively), mean summer and mean winter sea-surface salinities (SSS; respective RMSEP of 2.4 and 2.3 psu), and mean annual sea-ice cover (SIC) duration (RM-SEP of 1.2 months year −1 ).…”
Section: Sea-surface Conditionsmentioning
confidence: 56%
“…To complement our view of the system, we also compare our sea-surface hydrographical reconstructions with (i) the relative abundance of the mesopelagic polar planktonic foraminifera NPS obtained in the same cores (Eynaud et al, 2002;Zumaque et al, 2012;Wary, 2015) and considered as tracer of cold subsurface conditions (see Supplement Sects. S5 and S6 for further details; Carstens and Wefer, 1992;Bauch et al, 1997;Carstens et al, 1997;Hillaire-Marcel and Bilodeau, 2000;Volkmann and Mensch, 2001;Simstich et al, 2003;Hillaire-Marcel et al, 2004;Kretschmer et al, 2016), and (ii) Greenland ice core deuterium excess data as indicator of Greenland moisture origin (Masson-Delmotte et al, 2005).…”
Section: Complementary Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Previous paleoceanographic studies have demonstrated the high sensitivity of the Faeroe area to millennial-scale climatic variability and its intimate relation to the MOC dynamics (Rasmussen et al, 1996a(Rasmussen et al, ,b, 2002a(Rasmussen et al, ,b, 2008Thomsen, 2004, 2008;Eynaud et al, 2002;Voelker, 2002). During the last glacial period, the southern part of the Faeroe Islands was under the direct influence of the proximal European ice sheets (Fennoscandian ice sheet: FIS and the British-Irish ice sheet: BIIS) (Fig.…”
Section: Paleoclimatic Interestmentioning
confidence: 96%
“…1. Location of the studied core (MD99-2281: this work) and other cores discussed in the paper (MD95-2009;MD95-2010-Eynaud et al, 2002ENAM93-21 -Rasmussen and Thomsen, 2004;core SO82-5 -Van Kreveld et al, 2000;MD04-2822;MD95-2006-Knutz et al, 2001Hibbert et al, 2010;MD04-2829CQ -Hall et al, 2011. The yellow arrows depict the pathway of the main modern surface currents (Fogelqvist et al, 2003).…”
mentioning
confidence: 87%